The Effect of Clean and Healthy Lifestyle Education with Poster Media on the Level of Knowledge of Clean and Healthy Lifestyle and the Presence of Mosquito Flies in Geyer Village - Farah Fadhila; Adisty Rose Artistin (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Education on Clean and Healthy Living Behavior is considered important as an effort to prevent diseases transmitted through mosquito larvae, especially in areas with low levels of health awareness. The purpose of this study was to analyze the effect of Clean and Healthy Living Behavior education using poster media on the level of community knowledge and the presence of mosquito larvae in Geyer Village. This research method uses a quantitative approach with a pre-test-post-test design. The research location was in Geyer Village. The research was conducted in January-June 2024. The study population included all heads of families in Geyer Village, totaling 2,086 heads of families. The sampling technique was accidental sampling. The sample in this study was 95 family heads. Data collection can be done by using questionnaires in the form of interviews and observations. Data were analyzed using paired t-test, namely Dependent T-Test or Wilcoxon test. The results showed that there was an effect of Clean and Healthy Living Behavior education with poster media on the level of knowledge about Clean and Healthy Living Behavior and the presence of larvae in Geyer Village (p-value=0.000). Education on Clean and Healthy Living Behavior using poster media is effective in increasing community knowledge and reducing the presence of larvae, which in turn can contribute to efforts to prevent mosquito-borne diseases. In addition, education through posters also contributed to a decrease in the presence of larvae in the neighborhood. It is recommended that the Clean and Healthy Living Behavior education program be carried out in a sustainable manner by utilizing various media for optimal impact. Keywords: Hygiene and healthy lifestyle, Knowledge, Mosquito larvae